Anatomo-functional characterisation of the human "hand-knob": A direct electrophysiological study. (April 2019) - Viganò, Luca; Fornia, Luca; Rossi, Marco; Howells, Henrietta; Leonetti, Antonella; Puglisi, Guglielmo; Conti Nibali, Marco; Bellacicca, Andrea; Grimaldi, Marco; Bello, Lorenzo; Cerri, Gabriella
Abstract: The cortical area within the human primary motor cortex (M1) that hosts the representation of the hand and fingers is known as the 'hand-knob' and is essential for voluntary hand movement. The anatomo-functional heterogeneity described within the monkey primary motor cortex (M1) in a rostro-caudal direction suggests an internal subdivision in two sectors originating different systems of connections to the spinal cord. Direct investigation of the human hand-knob has been prevented, so far, by methodological constraints. The unique setting of brain tumour resection with the brain mapping technique in awake patients enables direct electrophysiological investigation of the functional properties of the human hand-knob. Motor-evoked potentials (MEPs) elicited by Direct Electrical Stimulation (DES) at high frequency (HF-DES) delivered along the hand-knob in rostro-caudal direction, i.e., from the central to the precentral sulcus, were recorded from the hand/arm muscles in patients at rest. The sites located near the precentral sulcus identified with HF-DES were then stimulated with low-frequency DES (LF-DES) during a hand manipulation task (HMt) to assess whether DES affected task execution. From the stimulated sites, corticofugal projections and U-shaped tracts connecting with adjacent gyri were traced using diffusion tensor and spherical deconvolution tractography. Analysis of MEPs showed a rostro-caudal gradient of cortical excitability along the hand-knob (the rostral sector being less excitable). Stimulation of rostral sites during the HMt impaired the task by inducing dysfunctional recruitment or, alternatively, suppression of distal muscles. Diffusion tractography showed different patterns of rostro-caudal connectivity for the U-shaped tracts. Overall data suggests, in humans, the anatomo-functional subdivision of the human hand-knob in two sectors, possibly subserving different roles in motor control.